PENGARUH KOMPOS DENGAN STIMULATOR EM 4 (EFFECTIVE MICROORGANISMS 4) TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays var, Saccharata) - Roihanna, Nur; Haryanti, Sri; Hastuti, Rini Budi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Production of sweet com, which is rich of carbohydrate, but less of protein and fat, still hasn’t fulfilled market needs. The increase of sweet com production may be carried out by improving the growth and production of this plant byproviding required hara element supply. This supply may be implemented by giving compost. The making of compost requires long time; it therefore should be added with stimulator EM4, namely liquid culture of microorganism like Lactobacillus, Actinomycetes and photosynthesis bacteria which may acceleratethe composing process. The problem formulation of this research is whether compost with EM4 stimulator influences the growth and producyion of sweet com and how many doze of compost with EM4 stimulator which may give the best result. The aim of the research is to evaluate the effect of compost with EM4stimulator against the growth and production of sweet com and also to evaluate the best doze of compost with EM4 stimulator which may gives the highest result. The research uses Complete Random Design with 4 treatments in which each treatment is repated 5 times. Those treatments are PO (control), P1 (compost 47,1 g/polybag), P2 (compost 94,2 g/polybag), P3 (compost 141,3 g/polybag). The obtained data was analyzed using ANOVA and BNT test when there is a significant difference.The result of the research indicates that compost with EM4 stimulator may increase the growth and production of sweet com and the doze of compost giving the highest result in the research is 141,3 g/polybag.